Risk of liver decompensation with cumulative use of mitochondrial toxic nucleoside analogues in HIV/hepatitis C virus coinfection. Issue 10 (19th July 2017) - Lo Re, Vincent; Zeldow, Bret; Kallan, Michael J.; Tate, Janet P.; Carbonari, Dena M.; Hennessy, Sean; Kostman, Jay R.; Lim, Joseph K.; Goetz, Matthew Bidwell; Gross, Robert; Justice, Amy C.; Roy, Jason A.
Abstract: Purpose: Among patients dually infected with human immunodeficiency virus (HIV) and chronic hepatitis C virus (HCV), use of antiretroviral therapy (ART) containing mitochondrial toxic nucleoside reverse transcriptase inhibitors (mtNRTIs) might induce chronic hepatic injury, which could accelerate HCV‐associated liver fibrosis and increase the risk of hepatic decompensation and death. Methods: We conducted a cohort study among 1747 HIV/HCV patients initiating NRTI‐containing ART within the Veterans Aging Cohort Study (2002‐2009) to determine if cumulative mtNRTI use increased the risk of hepatic decompensation and death among HIV‐/HCV‐coinfected patients. Separate marginal structural models were used to estimate hazard ratios (HRs) of each outcome associated with cumulative exposure to ART regimens that contain mtNRTIs versus regimens that contain other NRTIs. Results: Over 7033 person‐years, we observed 97 (5.6%) decompensation events (incidence rate, 13.8/1000 person‐years) and 125 (7.2%) deaths (incidence rate, 17.8 events/1000 person‐years). The risk of hepatic decompensation increased with cumulative mtNRTI use (1‐11 mo: HR, 1.79 [95% confidence interval (CI), 0.74‐4.31]; 12‐35 mo: HR, 1.39 [95% CI, 0.68‐2.87]; 36‐71 mo: HR, 2.27 [95% CI, 0.92‐5.60]; >71 mo: HR, 4.66 [95% CI, 1.04‐20.83]; P  = .045) versus nonuse. Cumulative mtNRTI use also increased risk of death (1‐11 mo: HR, 2.24 [95% CI, 1.04‐4.81]; 12‐35 mo: HR, 2.05 [95% CI, 0.68‐6.20]; 36‐71 mo: HR, 3.04 [95% CI, 1.12‐8.26]; >71 mo: HR, 3.93 [95% CI, 0.75‐20.50]; P  = .030). Conclusions: These findings suggest that cumulative mtNRTI use may increase the risk of hepatic decompensation and death in HIV/HCV coinfection. These drugs should be avoided when alternatives exist for HIV/HCV patients.